Sensitivity to House Dust Mites Allergens with Atopic Asthma and Its Relationship with CD14 C(-159T) Polymorphism in Patients of West Bengal, India. Issue 1 (17th October 2017) - Ghosh, Amlan; Dutta, Shampa; Podder, Sanjoy; Mondal, Priti; Laha, Arghya; Saha, Nimai Chandra; Moitra, Saibal; Saha, Goutam Kumar
Abstract: India is the home to around 15–20 million asthmatics, and asthma prevalence is increasing in Indian metropolitan area, including Kolkata, West Bengal. Complex interactions of genetic and environmental factors are involved in asthma. Genome-wide search for susceptible loci regulating IgE response (atopy) have identified a candidate gene CD14 which is most important in the context of allergic responses of respiratory system. This study was aimed to investigate the role of house dust and house dust mites in development of bronchial asthma and to explore the possible association of candidate gene CD14 with disease manifestation among Kolkata patient population. Skin-prick test was done among 950 asthmatic patients against 8 aeroallergens, including house dust and house dust mites and total serum IgE and allergen-specific IgE were measured. Polymerase chain reaction-restriction fragment length polymorphism was done in patients and nonasthmatic control ( n = 255 in each) to characterize a functional polymorphism, C(-159)T, of CD14, a positional candidate gene for allergy. We identified house dust as the most common aeroallergen sensitizer among atopic patients in Kolkata followed by Dermatophagoides pteronyssinus and Dermatophagoides farinae Hughes (Acari: Pyroglyphidae) mites. Patient's sera contain significantly higher IgE level than that of control. Allergen-specific IgE antibody test revealed that 76.36% patients had specific IgE antibody against D. pteronyssinus mite. There was a significant difference in the distribution of alleles and genotypes for CD14 polymorphism with an increase in disease severity. So, in Kolkata, house dust mite is a common aeroallergen and D. pteronyssinus is predominant among mites. The present study revealed that bronchial asthma has a genetic background.